A seroepidemiologic study of a measles outbreak, Yamagata Prefecture, Japan, 2017: The estimation of spreaders using serological assays in a measles elimination setting - Seto, Junji; Aoki, Yoko; Tanaka, Shizuka; Komabayashi, Kenichi; Ikeda, Tatsuya; Mizuta, Katsumi (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2022)
In regions where the endemic measles virus has been eliminated, early detection of contagious patients is important for preventing the spread of measles and sustaining elimination. To investigate whether serological assays can be used for the estimation of highly infectious patients with measles, we performed a seroepidemiologic study of a measles outbreak in Yamagata Prefecture, Japan, in 2017. We tested plaque reduction neutralization (PRN), IgG avidity, and gelatin particle agglutination (PA) assays in 31 patients with measles, subdivided into two super-spreaders, three spreaders, and 26 non-spreaders. Simultaneously, these results were compared with the cycle threshold (Ct) of a semi-quantitative real-time reverse transcription PCR for the measles virus from throat swab specimens. In the PRN assay, one super-spreader and two spreaders lacked protective antibodies. The IgG avidity assay showed that two super-spreaders and one spreader had low avidity. The PA assay indicated that two super-spreaders and two spreaders lacked protective antibodies. Comparison of the results of the three serological assays and Ct revealed that patients whose antibody titers were judged as low in the IgG avidity and PA assays showed low Ct (i.e., high viral load), whereas non-spreaders tended to show low viral load. Our preliminary seroepidemiologic analysis of a population of 31 patients with measles suggests that PA and IgG avidity assays may be used for the identification of super-spreader/spreader candidates. However, further investigations are necessary to validate the robustness of these serological assays in detecting contagious measles cases.